posted by K.C .
Evaluate the difference quotient
A.) f(x)= 3x -1
so far i have done this
f(x+h) = 3(x+h)-1
b.) f(x)=2X^2 + 3X
i have done this f(x+h)= 2(x+h)+3(x+h)
im not sure if my answers are right.. just need some advice if they are wrong and explain what i did wrong
i just noticed i forgot to divide by h and forgot the -f(x):ooooooo but still can anyone post the answers so i know if im doing this right or wrong
is that really F(x)= (x+h)-f(x) or F(x)= f(x+h)-f(x) ? *the f(x+h)*
A.) that's right. f(x+h) = 3(x+h)- 1
B.) you forgot to raise 2(x+h).. by 2.
also for the -f(x) in the different quotient i think i also forgot to insert 3x-1 and 2x^2+3x into my equation.... anyone
-f(x) means you just have to multiply every term by -1, like for (A)
-(3x-1) = -3x + 1
try it to letter (B). :)
then substitute the answers you get into the F(x).